Death by chocolate lab eaudiobook - Blake, Bethany (Lucky Paws Petsitting Mystery, 2018)
Pet sitter Daphne Templeton has a soft spot for every stray and misfit who wanders into the quaint, lakeside village of Sylvan Creek. But even Daphne doesn't like arrogant, womanizing Steve Beamus, the controversial owner of Blue Ribbon K-9 Academy. When Steve turns up dead during a dog agility trial, Daphne can think of a long list of people with motives for homicide, and so can the police. Unfortunately, at the top of the list is Daphne's sister, Piper—Steve's latest wronged girlfriend. Certain that Piper is innocent, in spite of mounting evidence to the contrary, Daphne sets out to clear her sister's name—and find Axis, Steve's prize-winning chocolate Labrador, who went missing the night of Steve's death. Aided by Socrates, her taciturn basset hound, and a hyperactive one-eared Chihuahua named Artie, Daphne quickly runs afoul of Detective Jonathan Black, a handsome and enigmatic newcomer to town, who has no appreciation for Daphne's unorthodox sleuthing. Can a free-spirited pet sitter, armed only with a PhD in philosophy and her two incompatible dogs, find the real killer before she becomes the next victim?